NSs, the Silencing Suppressor of Tomato Spotted Wilt Orthotospovirus, Interferes With JA-Regulated Host Terpenoids Expression to Attract Frankliniella occidentalis - Du, Jiao; Song, Xiao-yu; Shi, Xiao-bin; Tang, Xin; Chen, Jian-bin; Zhang, Zhan-hong; Chen, Gong; Zhang, Zhuo; Zhou, Xu-guo; Liu, Yong; Zhang, De-yong (Frontiers in Microbiology, 2020)
Tomato spotted wilt orthotospovirus (TSWV) causes serious crop losses worldwide and is transmitted by Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae). NSs protein is the silencing suppressor of TSWV and plays an important role in virus infection, cycling and transmission process. In this research we investigated the influences of NSs protein on the interaction of TSWV, plants and F. occidentalis with the transgenic Arabidopsis thaliana. Compared with wild-type Col-0 plant, F. occidentalis showed the increased number and induced feeding behavior on transgenic Arabidopsis thaliana expressing exogenous NSs. Further analysis showed that NSs reduced the expression of terpenoids synthesis-related genes and the content of monoterpene volatiles in Arabidopsis. These monoterpene volatiles played a repellent role in respect of F. occidentalis. In addition, the expression level of plant immune-related genes and the content of the plant resistance hormone jasmonic acid (JA) in transgenic Arabidopsis were reduced. The silencing suppressor of TSWV NSs alters the emission of plant volatiles and reduces the JA-regulated plant defenses, resulting in enhanced attractiveness of plants to F. occidentalis and may increase the transmission probability of TSWV.